1993
DOI: 10.1007/bf01976760
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acetylsalicylic acid on aListeria monocytogenes infection

Abstract: The influence of acetylsalicylic acid (ASA, CAS 50-78-2) on the Listeria monocytogenes infection in balb/c mice was investigated. One day prior to lethal or sublethal infection, balb/c mice were treated intravenously with therapeutic concentrations of ASA alone or ASA in combination with murine recombinant interferon gamma, a lymphokine produced by T-helper cells. Three days post-infection, parasite burdens of spleen and liver were determined by the colony-forming unit assay. It was shown that the prophylactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The slightly lower values with extracts from IBU-loaded membranes were unexpected, as several reports have shown no cytotoxicity of IBU for higher concentrations. 57,58 Overall, this assay demonstrated that the scaffolds were compatible with biomedical applications and no acute toxicity was observed.…”
Section: Resultsmentioning
confidence: 74%
“…The slightly lower values with extracts from IBU-loaded membranes were unexpected, as several reports have shown no cytotoxicity of IBU for higher concentrations. 57,58 Overall, this assay demonstrated that the scaffolds were compatible with biomedical applications and no acute toxicity was observed.…”
Section: Resultsmentioning
confidence: 74%
“…ASA was able to reduce bacterial burden in mice infected with L. monocytogenes . Specifically, the prophylactic administration of ASA in a concentration of 5 mg/kg body weight resulted in a more than 10-fold reduction in L. monocytogenes [ 34 ]. Yang et al [ 35 ] analyzed a retrospective study of Sedlacek et al [ 36 ] which stated that a high dose of ASA (324 mg) rather than a low dose (81 mg) was associated with a decreased risk of S. aureus infection in hemodialysis patients.…”
Section: Resultsmentioning
confidence: 99%